2016
DOI: 10.14238/sp18.2.2016.111-6
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Terapi dan Luaran Infeksi Saluran Kemih oleh Bakteri Penghasil Extended Spectrum Beta Lactamase pada Anak di RSUD Dr. Soetomo Surabaya

Abstract: Latar belakang. Kasus infeksi saluran kemih oleh bakteri penghasil extended spectrum beta-lactamase (ESBL) dilaporkan sudah banyak terjadi di dunia. Informasi terkait ESBL di Indonesia sangat sedikit, terutama pada pasien anak. Tujuan. Mengkaji gambaran terapi serta luaran pasien infeksi ESBL di RSUD Dr. Soetomo Surabaya periode Januari-Juni 2014. Metode. Penelitian observasional dengan studi deskriptif, digunakan data rekam medis pasien anak RSUD Dr. Soetomo Surabaya periode Januari-Juni 2014. Variabel peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
0
0
2
Order By: Relevance
“…ESBL is a group of enzymes that have the hydrolysis and inactivation capabilities of beta-lactam antibiotics, including thirdgeneration cephalosporin, penicillin and aztreonam (Enany et al, 2020). Previous research studies supported the type of ESBL-producing bacteria found in this study also carried out at Dr. Soetomo General Hospital Surabaya by Irawan et al (2012) which got K. pneumonia 52.08% and E. coli 47.92% and studies with pediatric patients at the same location obtained K. pneumonia with ESBL 60.7% and E. coli with ESBL 37.5% (Muhajir et al, 2016). The ESBL bacteria problem is not only experienced in Indonesia, but research in Nepal also shows the same results K. pneumoniae 44%, P. aeruginosa 29%, E. coli 20% (Rooku et al, 2019).…”
Section: • Opportunistic Bacterial Infection In Hiv Patientsupporting
confidence: 84%
“…ESBL is a group of enzymes that have the hydrolysis and inactivation capabilities of beta-lactam antibiotics, including thirdgeneration cephalosporin, penicillin and aztreonam (Enany et al, 2020). Previous research studies supported the type of ESBL-producing bacteria found in this study also carried out at Dr. Soetomo General Hospital Surabaya by Irawan et al (2012) which got K. pneumonia 52.08% and E. coli 47.92% and studies with pediatric patients at the same location obtained K. pneumonia with ESBL 60.7% and E. coli with ESBL 37.5% (Muhajir et al, 2016). The ESBL bacteria problem is not only experienced in Indonesia, but research in Nepal also shows the same results K. pneumoniae 44%, P. aeruginosa 29%, E. coli 20% (Rooku et al, 2019).…”
Section: • Opportunistic Bacterial Infection In Hiv Patientsupporting
confidence: 84%
“…Leukosit esterase merupakan suatu keadaan dimana terdapatnya leukosit yang mengeluarkan enzim esterase yang disebabkan oleh adanya bakteri golongan Enterobacteriaceae. 5,6 Kultur urin merupakan pemeriksaan baku emas untuk mendiagnosis ISK, interpretasi hasil dengan menghitung jumlah kuman yang ada pada media kultur. 7 Pada anak, ISK merupakan infeksi yang paling sering terjadi setelah infeksi saluran napas.…”
Section: Pendahuluanunclassified
“…Extended Spectrum Beta-Lactamase (ESBL) adalah enzim hidrolitik yang dimiliki kelompok bakteri Gram negatif sepeti E. coli dan Klebsiella spp. untuk menghidrolisis cincin beta laktam (Muhajir at al., 2016). Apabila cincin tersebut lisis, maka akan terjadi peningkatan resistensi bakteri terhadap antibiotik, seperti penicillin ataupun kelompok antibiotik aztreonam (Katzung, 2002).…”
Section: Pembahasanunclassified